?-Glucosidase Inhibitory Activity of In Vitro Combination of 96% Ethanolic Extract of Brotowali Stem (Tinospora cordifolia) and Cashew Apple (Anacardium occidentale L.) - Wanudya Atmajani; Ahya Nafila Fatihati; Afifah Mujahidah Shalihah; Ika Trisharyanti Dian Kusumowati (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2018)
Cashew tree (Anacardium occidentale L), contains flavonoid compound which plays a role in the medical treatment of Diabetes Mellitus because this compound has activity as an ?-glucosidase inhibitor. Brotowali stem extract (Tinospora cordfolia) demonstrated ?-glucosidase inhibitory (AGIS) activity. This research aimed to measure 96% ethanolic extract AGIS activity of brotowali-cashew apple combination (BJM). The research was conducted by using ELISA reader instrument at 405 nm for AGIS activity test. The IC50 was calculated from each sample. The IC50 of brotowali stem and cashew apple was 34,61 ?g/ml and 109,32 ?g/ml. Then, the combination of brotowali and cashew apple extract was mixed with each concentration of 0,5%. From 1:0, 1:2, 1:1, 2:1, and 0:1 BJM comparison resulted in AGIS power percentage averages of 84.05%, 69.51%, 70.92%, 68.10%, 40.37%. The results of this research indicated that brotowali stem has the potential as AGIS, while cashew apple has not any potential towards AGIS and that extract combination does not give synergic effect. Therefore, the use of a combination of brotowali-cashew apple extract is not as effective as the use of brotowali single extracts to inhibit the ?-glucosidase enzyme